Near-field assisted nanoscale patterning for improved absorption in thin film silicon solar cell - Murukeshan, V. M. (2015)
Near field optics concepts have introduced a paradigm shift in a wide variety of engineering fields in the recent past and the most significant applications of this fundamental physics concepts have been in the applied engineering problems such as improved broad band light absorption thereby enhancing the conversion efficiency of thin silicon solar cells. Also, for writing patterned structures or features using non contact optical methodologies have enabled near field optics assisted fabrication and related applications. The technology involving optics concepts and methodologies targeting energy sector have seen the impact of the same with a challenging trend to achieve smaller features or devices with micro- or nano-scale features. This demands automatically the need for achieving much smaller features beyond the forecasted sub- 30nm feature patterning methodologies. To meet such demands, a new branch of near- field optical concepts for improving patterning resolution has started developing which have been receiving considerable attention for its ability to produce high density sub-wavelength features that can find tremendous energy harvesting applications. This paper in this context mainly focuses on the review of different near field optical concepts and approaches developed for patterning by the author’s group at NTU. Different concepts were explored incorporating surface Plasmon waves ( LSPs, SPPs, LRSPs), gap modes as well as their interference in order to high resolution features and pattern dimensions at nano-scales. The absorbance of near band gap light is small and hence structuring of thin film solar cell is very important for increasing the absorbance by light trapping. The manuscript conclude by correlating the above said aspects and the challenges in achieving improved light conversion in thin film solar cells.